Técnicas de limpieza bronquial en pacientes con bronquiolitis. - Castro Vaca, Verónica Lisseth (2025)
Introduction: Bronchiolitis is a respiratory condition that mainly affects children under 2 years of age and affects children under 6 months of age. It is characterized by respiratory distress, airway obstruction and accumulation of secretions. Treatment focuses on relieving symptoms, maintaining oxygenation and helping to clear the airways through bronchial cleansing techniques. Objective: To investigate the different bronchial clearance techniques in the management of patients with bronchiolitis by identifying practices that improve respiratory symptoms to reduce associated complications. Methodology: The research was documentary and bibliographic based on databases such as Medline, Scopus, Cochrane, selecting studies from the last 10 years, rated on the Physiotherapy Evidence Database (PEDro) scale with a score greater than or equa to 6 points. Results: A total of 80 articles were collected, 25 of which were selected after filtering and analysis. Conclusion: Prolonged slow expiration facilitates clearance of secretions due to increased expiratory volume, improving ventilation and oxygenation. On the other hand, continuous positive airway pressure ventilation (CPAP) and high-flow nasal cannula (HFNC) provide respiratory support, with CPAP being effective but invasive in chronic patients, while HFNC is a less invasive alternative. Finally, nasal saline nasal lavage allows the nasal passages to be cleared, thus aiding breathing and oxygen saturation.